USING INTERACTIVE MEDIA OF SPOTIFY IN SPEAKING THROUGHT SONG LYRIC COMPREHENSION FOR STUDENTS IN SENIOR HIGH SCHOOL - Bunga Herjenita; Bunga Sapira; Liza Anggun Oktia (PT. Intelek Cendikiawan Nusantara, 2024)
This study investigates how senior high school students' use of Spotify as an interactive media tool can improve their English-speaking abilities. Given that speaking is an essential communication skill, the study looks into how vocabulary, pronunciation, and confidence can be increased by using Spotify song lyrics. A qualitative methodology was used with thirty carefully chosen SMA students from Pagar Alam, ages fifteen to eighteen. During the flipped classroom process, data were gathered through quiet participant observation and in-depth interviews. The results show that students' speaking skills have significantly improved, confirming the value of interactive media in language acquisition. Notwithstanding several constraints, such a limited sample size and a brief assessment period, the research indicates that incorporating Spotify into language courses can prove to be a beneficial tactic for improving oral proficiency. It is advised that bigger, more varied sample sizes and longer study durations be used in future research to verify these findings and investigate the long-term impacts of interactive media on language learning.